Special Characteristics of the Marriage Contract in Family Law - Bayjanova Ramuza Tenelbay qizi; Allambergenova Zamira Rasbergen qizi (European Science Publishing, 2024)
The article presents the legal regulation and order of the marriage contract, the history of the marriage contract, its application in the practice of foreign countries, the formation of the institution of the marriage contract, and the specific features of the marriage contract.
Keywords: marriage, family, marriage contract, Western and Eastern Europe, marriage contract, courts of justice, Family Code, category of will, Commodity-money relations.